The Effectiveness of the Green Design and Manufacturing Decision in Achieving the Outstanding Performance of the Industrial Companies: An Analytical Study in Al-Zawraa General Company - Ikhlas Satar Oglah (Journal of Techniques)
The objective of this research is to analyze the impact of product design decisions and green manufacturing on Al-Zawraa General Company's competitive advantage in Iraq. Data was collected through a questionnaire that measured key variables، such as product design، green manufacturing، and outstanding performance. Each major variable was further evaluated through three sub-dimensions. Out of the 75 employees invited to participate، 60 staff responded to the questionnaire. Quantitative and qualitative methods، such as arithmetic means، standard deviations، and confirmatory factor analysis، were employed to examine the effect of the key variables in implementing the green manufacturing system in the company.  The study's findings suggest that the company's management should reconsider its approach to green technology by implementing modern automation methods that utilize environmentally friendly energy sources. This change would not only help to reduce industrial pollution rates and benefit the environment but also enhance the company's appeal to consumers and ensure its longevity and competitiveness in the local and global industrial markets. Furthermore، the study revealed a strong correlation between the key variables and the successful adoption of the green manufacturing system.